Teams at the top : unleashing the potential of both teams and individual leaders - Katzenbach, Jon R., 1932- (Boston, Mass. : Harvard Business School Press, 1998)
Teams at the Top shows how even the strongest and most successful CEO can improve the performance of various leadership groupings by enabling senior executives and next-level leaders to function as real teams as well as single-leader units - all without sacrificing each member's individual leadership capabilities and results. Teams at the Top explains how to recognize when a team effort at the upper management level is preferable and when a working group under single leadership fits best. Then, the book demonstrates how to develop the capability to shift into whichever mode is appropriate to the task at hand, integrating the discipline required for real teams with the discipline needed for executive leadership without compromising one in favor of the other.
With stories and examples from well-known companies - including Enron, Ben & Jerry's, Champion, Citicorp, and Mobil - and lessons that are applicable for management groups throughout the organization, this book will help companies of all sizes and in all industries maximize the full potential of their leadership.
Introduction: The Spirit of Haida Gwaii -- 1. A Tougher Game at the Top -- 2. Why "Nonteams" Prevail at the Top -- 3. How "Major Events" Spawn Teams -- 4. Two Disciplines That Conflict -- 5. Collective Action Opportunities -- 6. Making Key Tradeoffs Consciously -- 7. Multiple Roles for the CEO -- 8. For "Teams That Run Things" at Any Level -- 9. Discipline, Alignment, and Balance -- App. A. A Glossary of Team Terms -- App. B. Team Discipline Reprise -- App. C. Diagnostic Guide: Obtaining Team Performance When It Counts.
Includes bibliographical references (pages 223-226) and index.
Print version record.
Keywords: Teams in the workplace; Leadership; Équipes de travail; Leadership; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS -- Corporate Governance; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- Organizational Development; Leadership; Teams in the workplace; elektronické knihy; electronic books